Design and Concept Selection of a Modular EV Conversion Kit for Automatic Motorcycles with the Bahana Nusantara Hijau Theme for Mobility in Indonesia - Patrisius Edi Prasetyo; M. Fahrudin Al Fadli (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2025)
Urban air pollution, primarily driven by emissions from conventional motorcycles, remains a critical environmental and public health issue in Indonesia. Although the government has introduced various incentive programs, the nationwide adoption of electric motorcycles (EMs) is still limited due to challenges such as inadequate battery range, long charging times, and high initial investment. This research introduces a modular electric vehicle (EV) conversion kit engineered for existing internal combustion engine motorcycles (ICEm), offering a hybrid propulsion system that enables seamless switching between electric drive and fuel-based operation. The development process employs Ulrich and Eppinger’s product development methodology, systematically progressing through concept generation, concept selection, and 3D modeling stages. A total of 72 design alternatives were generated using black-box and transparent-box modeling, internal-external searches, and morphological analysis. Through classification trees and multivoting techniques, the options were refined to 12 concepts and evaluated using a weighted scoring matrix. Concept code 34 was selected based on criteria such as performance, manufacturability, cost-effectiveness, and user ergonomics. The final 3D model, created using Autodesk Inventor 2025, integrates a culturally inspired aesthetic—Bahana Nusantara Hijau—to reinforce local identity. This modular kit offers a viable, low-barrier solution to accelerate EM adoption and promote sustainable mobility in Indonesia.